Penguatan identitas lokal dan penolakan vigilantisme atas nama agama - Manggala Ismanto (Faculty of Social and Political Science, Universitas Airlangga, 2017)
After the reformation, the strengthening of local identity has sprung up in several regions in Indonesia. The movement produced the revitalization of adat. These movements underlining the effort from communities which affiliated with a particular ethnic identity to gain claims of management of the natural and political-economic resources in their region. Contestation between the indigenous Dayak community and ‘Front Pembela Islam” (FPI) that occurred in Palangkaraya was a phenomenon that shows how indigenous people were able to assert its right to manage security and morality in their own society. The discourse of FPI’s establishment which often associated with vigilantism brought resistance and the refusal from Dayak community in Central Kalimantan. Through demonstrations, DAD and the indigenous Dayak community was able to exclude FPI from Palangkaraya. Thus, this research aims to analyze (1) the history of ethnic and religious identity movements in Indonesia after the reformation and (2) how the contestation between indigenous Dayak community and FPI occurred in the local context according to identity recognition and legitimation. This research used qualitative approach; data gathered through field observation and unstrucutred interviews. The research concludes that there is an awareness in the community to negotiate their position as an opposition to the occurence of a group with particular ideology, which has become the research highlight. This was proven by the case in Palangkaraya that vigilantism on the name of religion is not supposed to be maintain because it violates the right of other group.